Composition Chimique Et Activité Antimicrobienne Des Huiles Essentielles De Deux Espèces De Lavande : Lavandula Dentata Spp. Dentata Et Lavandula Peduncultata Spp. Pedunculata - Lamia Bachiri; Mohamed Bammou; Ghizlane Echchegadda; Jamal Ibijbijen; Lhoussaine El Rhaffari; Zoubida Haloui; Laila Nassiri (European Scientific Journal, ESJ, 2017)
The aim of the present work is to compare the chemical composition, antibacterial and antifungal activity of two spontaneous species of lavender "Lavandula stoechas L." and "Lavandula dentata L." in Morocco. A phytochemical screening was performed on the aerial part of invested plants. The qualitative variation was revealed in the secondary metabolites of the species studied. Subsequently, the dosage of the crude organic extracts showed that the polyphenol content was higher in the methanol fraction, with an important yield in L. dentata. Also, the essential oils of the aerial part, obtained by hydrodistillation gave higher yields in L. dentata than L. pedunculata. Finally, tests of the antibacterial and antifungal activity of the essential oils of the two species were performed on four strains of bacterial pathogens (Staphylococcus aureus "Gram+," and Escherichia coli; Klebsiella pneumoniae and Proteus mirabilis which are Gram-), and three phytopathogenic fungi : Rhizopus stolonifer, Aspergillus brasiliensis and Penicillium expansum, The results obtained showed that the essential oil of L. dentata showed a strong antibacterial activity against the studied strains, particularly against S. aureus. While the antifungal activity revealed that L. pedunculata has a remarkable antifungal power against the fungi tested in comparison with L. dentata.